Legal Implications of the Constitutional Court Decision No. 18/PUU-XI/2013 on Simplifying Birth Certificate Registration Procedures in Indonesia - Maulana, Esty; Amir, Irfan; Sari, Muspita; Aris, Ismail (Constitutional Law Review, 2024)
This study analyzes the legal implications of the Constitutional Court Decision Number 18/PUU-XI/2013 on Indonesia's birth certificate registration, particularly for late registrations exceeding one year. Prior to this decision, late registrations required a court decree from the District Court, creating a significant burden for the public. The Court's ruling eliminated the need for a court decree, transferring full authority to the Civil Registry Office (Disdukcapil) for issuing late birth certificates. This decision introduces a fundamental shift in the registration process, simplifying administrative procedures and improving public access to civil registration services. However, it also presents challenges related to the validity of documents issued by Disdukcapil. The study finds that Disdukcapil must enforce rigorous verification procedures to ensure the legitimacy of birth certificates and prevent misuse. The findings indicate that the Court's decision positively impacts public access to essential services but highlights the necessity for strict oversight and enhanced service quality at Disdukcapil. These measures are crucial for ensuring that the decision effectively delivers fair and reliable legal protection for all citizens.